Software Engineering Education : SEI Conference 1991 Pittsburgh, Pennsylvania, USA, October 7–8, 1991 Proceedings - Tomayko, James E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 1991)
The Fifth SEI Conference on Software Engineering was held in Pittsburgh, Pennsylvania, October 7-8, 1991. This annual conference is a forum for discussion of software engineering education and training among members of the academic, industry, and government communities. It is funded by the Education Program of the Software Engineering Institute, a federallyfunded research and development center of the U.S. Department of Defense. For the first time in 1991 it was held in conjunction with the Association for Computing Machinery and the IEEE Computer Society. Seven sessions addressed: software project courses, software engineering training in government and industry, curriculum issues, software engineering teaching styles, teaching design, topics inreal time and environments, and developing software engineering expertise.
Keynote address -- Medium size project model: Variations on a theme -- A controlled software maintenance project -- Models for undergraduate project courses in software engineering -- The establishment of an appropriate software engineering training program -- Industrial training for software engineers -- Software engineering: Graduate-level courses for AFIT professional continuing education -- Computing curricula 1991 its implications for software engineering education -- Computer based systems engineering workshop -- Teaching about process issues in software engineering -- A layered approach to teaching software project management -- Seven lessons to teach design -- Design evolution: Implications for academia and industry -- Teaching software design in the freshman year -- Teaching software engineering for real-time design -- Industry-academia collaboration to provide CASE tools for software engineering classes -- Developing se expertise -- What we have learned about software engineering expertise -- Instruction for software engineering expertise -- Knowledge elicitation for software engineering expertise.
SpringerLink.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Software Engineering